Existing regional co-operation in the Caribbean (between DFA's and ACP's) and in the Indian Ocean (The Council LondonGB, 1996)
Highlights areas of regional cooperation and initiatives undertaken in the Caribbean and the Indian Ocean. Lists some of the projects implemented, or are being implemented under the Lome Conventions, by sector and EDF number.
DC